2019
DOI: 10.1002/btpr.2778
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid‐encoded protein attenuates Escherichiacoli swimming velocity and cell growth, not reprogrammed regulatory functions

Abstract: In addition to engineering new pathways for synthesis, synthetic biologists rewire cells to carry out "programmable" functions, an example being the creation of wound-healing probiotics. Engineering regulatory circuits and synthetic machinery, however, can be deleterious to cell function, particularly if the "metabolic burden" is significant. Here, a synthetic regulatory circuit previously constructed to direct Escherichia coli to swim toward hydrogen peroxide, a signal of wound generation, was shown to work e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Beyond toxicity and sufficiency for activating a genetic response, was the finding that E. coli cells could rapidly consume/degrade hydrogen peroxideeven when 50 μM was added to cultures at OD 600 ∼ 0.1. 43 That said, after mixing both transmitter and receiver cells together at fixed ratios and cell densities, we found that an initial OD 600 of 0.1 was optimal for generating GFP and for minimizing deleterious effects on growth (data not shown) in response to a range of hydrogen peroxide concentrations (typically less than 50 μM). Then, using the same electrochemical cell as described above, we introduced cells into the ORR cell, biased the electrode to −0.5 V vs Ag/AgCl for specified times, and then followed cell growth and gene expression for 3 h in a 37 °C 250 rpm shaker.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…Beyond toxicity and sufficiency for activating a genetic response, was the finding that E. coli cells could rapidly consume/degrade hydrogen peroxideeven when 50 μM was added to cultures at OD 600 ∼ 0.1. 43 That said, after mixing both transmitter and receiver cells together at fixed ratios and cell densities, we found that an initial OD 600 of 0.1 was optimal for generating GFP and for minimizing deleterious effects on growth (data not shown) in response to a range of hydrogen peroxide concentrations (typically less than 50 μM). Then, using the same electrochemical cell as described above, we introduced cells into the ORR cell, biased the electrode to −0.5 V vs Ag/AgCl for specified times, and then followed cell growth and gene expression for 3 h in a 37 °C 250 rpm shaker.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…In the single cell case, L-DOPA was formed as expected but the yields were low and inconsistent (data not shown). Perhaps, this was a case in which our desired function overburdened the redirection capacity of a single cell. Instead, we focused our efforts on the coculture system wherein each plasmid of an AND logic gate was expressed in separate “catalytic” and “reagent” cell populations (Figure A). To test the ability of our cell network to produce an L-DOPA signal, we incubated a coculture of pSox-Tyrosine reagent transducer cells and tyrosinase-expressing catalytic transducer cells with varying amounts of paraquat and periodically measured the L-DOPA signal in the conditioned media with cyclic voltammetry.…”
Section: Resultsmentioning
confidence: 99%